2019
DOI: 10.1002/cplu.201900245
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Depolymerization of Oligomers during Thermal Cracking of Silicon‐Containing Carbamates

Abstract: Polymerization reactions in the thermal cracking of N‐substituted carbamates to produce the corresponding isocyanates significantly reduce the yield of isocyanates and thus vastly hinder the industrial application of such non‐phosgene routes. Herein, we tried to recycle the oligomers generated during the thermal cracking of 3‐ethylcarbamatopropyltriethoxysilane (CPTS) to produce 3‐isocyanatopropyltriethoxysilane (IPTS). Firstly, the polymerized substrates of the pyrolysis reaction were analyzed by NMR, IR, MAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Then they heated the mixture of products in the presence of urea and alcohols at 190 °C to get the recycled product of silicone‐containing carbamate. They were able to recover 96% by mass by this cycling procedure 127 …”
Section: Catalytic Depolymerization From 110 To 350 °Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Then they heated the mixture of products in the presence of urea and alcohols at 190 °C to get the recycled product of silicone‐containing carbamate. They were able to recover 96% by mass by this cycling procedure 127 …”
Section: Catalytic Depolymerization From 110 To 350 °Cmentioning
confidence: 99%
“…They were able to recover 96% by mass by this cycling procedure. 127 Polysiloxane depolymerization can also occur using acid chlorides, acetic acid or methanol in the presence of cheap iron salts at 190 °C. Enthaler explored the recyclability of siloxanes using these methods and found that, when he used acid chlorides with Fe catalyst, he got dichlorodimethylsilane as the primary product.…”
Section: Nucleophilesmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible dissociation mechnism of polyurea[28] (color online).图 8 (a) 光气法生产异氰酸酯过程; (b) 非光气制异氰酸酯三步过程(网络版彩图) (a) Phosgene process for isocyanate; (b) three-step non-phosgene process for isocyanate production (color online).…”
mentioning
confidence: 99%